Molecular Mechanisms of Skeletal Muscle Atrophy in a Mouse Model of Cerebral Ischemia. Issue 6 (June 2015) - Desgeorges, Marine Maud; Devillard, Xavier; Toutain, Jérome; Divoux, Didier; Castells, Josiane; Bernaudin, Myriam; Touzani, Omar; Freyssenet, Damien Gilles
<x xml:space="preserve">Abstract</x> Background and Purpose— Loss of muscle mass and function is a severe complication in patients with stroke that contributes to promoting physical inactivity and disability. The deleterious consequences of skeletal muscle mass loss underline the necessity to identity the molecular mechanisms involved in skeletal muscle atrophy after cerebral ischemia. Methods— Transient focal cerebral ischemia (60 minutes) was induced by occlusion of the right middle cerebral artery in C57BL/6J male mice. Skeletal muscles were removed 3 days later and analyzed for the regulation of critical determinants of muscle mass homeostasis (Akt/mammalian target of rapamycin pathway, myostatin-Smad2/3 and bone morphogenetic protein-Smad1/5/8 signaling pathways, ubiquitin-proteasome and autophagy-lysosome proteolytic pathways). Results— Cerebral ischemia induced severe sensorimotor deficits associated with muscle mass loss of the paretic limbs. Mechanistically, cerebral ischemia repressed Akt/mammalian target of rapamycin pathway and increased expression of key players of ubiquitin-proteasome pathway (MuRF1 [muscle RING finger-1], MAFbx [muscle atrophy F-box], Musa1 [muscle ubiquitin ligase of SCF complex in atrophy-1]), together with a marked increase in myostatin expression, in both paretic and nonparetic skeletal muscles. The Smad1/5/8 pathway was also activated. Conclusions— Our data fit with a model in which a repression of Akt/mammalian target of rapamycin pathway and an increase in the expression of key players of ubiquitin-proteasome pathway are critically involved in skeletal muscle atrophy after cerebral ischemia. Cerebral ischemia also caused an activation of bone morphogenetic protein-Smad1/5/8 signaling pathway, suggesting that compensatory mechanisms are also concomitantly activated to limit the extent of skeletal muscle atrophy.